Clinical Effects of Mindfulness-Based Intervention in Patients With First Episode Psychosis and in Individuals With Ultra-High Risk for Transition to Psychosis: A Review - Vignaud, Philippe; Reilly, Karen T.; Donde, Clément; Haesebaert, Frédéric; Brunelin, Jérôme (Frontiers in Psychiatry, 2019)
Objectives: Recent clinical studies and meta-analyses have reported the clinical effects of mindfulness-based interventions as a complementary treatment for patients with schizophrenia, but their possible efficacy in patients with first episode of psychosis (FEP) and in individuals with ultra-high risk (UHR) of transition to psychosis is less clear. Here, we investigated the current evidence on the usefulness of mindfulness-based interventions in these two populations. Methods: We conducted a systematic search of the literature according to the PRISMA guidelines. Results: Among the 102 references retrieved, 9 responded to the inclusion criteria (8 in FEP patients and 1 in UHR individuals). In FEP patients, mindfulness interventions are well-tolerated and have a satisfactory level of adherence. The clinical benefits consist primarily of reduced anxiety and sadness and improved quality of life. None of the studies reported any increase in positive symptoms. Conclusion: Future sham-controlled studies with large sample sizes are needed to definitively conclude on the clinical interest of mindfulness-based interventions in FEP patients and UHR individuals as well as to understand their underlying mechanisms of action.